Cerefy Student brain atlas - Nowinski, Wieslaw L.; Thirunavuukarasuu, A.; Bryan, R. Nick ([S.l. : s. n.], 2001)
The Cerefy Student Brain Atlas ia a remarkable accomplishment combining the best of current neuroanatomical methodology with the amazing capability of the modern personal computer.
System requirements: CD-ROM drive ; 32 MB of installed RAM (64 MB or greater recommended) Pentium III recommrnded Windows 95, 98, 2000, NT 4.0 or later
Keywords: Brain -- atlases